Theories about the Idea of Freedom and Their Epistemological Analysis (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
The article explores the philosophical aspects and social significance of the idea of freedom, which is the product of human thought. An analysis of the processes taking place in political and cultural life today reveals that the subject is a global problem.